2021
DOI: 10.3390/su131910581
|View full text |Cite
|
Sign up to set email alerts
|

Research Insights and Challenges of Secondary School Energy Education: A Dye-Sensitized Solar Cells Case Study

Abstract: The research achievements of a university chemistry lab regarding dye-sensitized solar cells (DSSCs) were transformed into a high school hands-on course by simplifying the experimental steps and equipment. Our research methodology was action research. We verified the DSSC course step by step. First, 10 members of a high school science study club helped to revise the course over a school semester. A questionnaire survey revealed that all students agreed that the course increased their understanding of DSSCs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, simply introducing the curricula would be insufficient if the teaching and learning approaches fail to explore active learning involving the community, home, and technological factors. The curricula must also feature multidisciplinary concepts [40,41] that integrate all the mentioned factors before introducing the curricula into the secondary education spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, simply introducing the curricula would be insufficient if the teaching and learning approaches fail to explore active learning involving the community, home, and technological factors. The curricula must also feature multidisciplinary concepts [40,41] that integrate all the mentioned factors before introducing the curricula into the secondary education spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The educational strategies employed were active, interactive, game-based, project-based, experiential, action-based, collaborative, problembased, and multidisciplinary learning strategies (Table 3). The results indicated that the introduction of such content on RE and sustainable development concepts increased the overall interests of the students in RE concepts and STEM subjects, motivated them to learn more about the environmental issues and how to address them, increased their knowledge about RE concepts, and increased their awareness about the necessity of environmental safety and the different strategies for harnessing green and clean environmentally benign energy [20,27,28,30,36,[39][40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations